Kepemimpinan Berbasis Hasil dalam Pendidikan: Penerapan Teknik Kepemimpinan di SMP Negeri 12 Yogyakarta - Tobasa, Majelis Rena; Masduki, Yusron; Meysihinur, Meysihinur; Azizah, Nurul (YASIN, 2023)
This research investigates the implementation of results-based leadership in an educational context, with a case study at SMP Negeri 12 Yogyakarta. The background to this research identifies the need for effective leadership in improving the quality of education in Indonesia. The aim of this research is to understand the results-based leadership practices implemented by school principals at SMP Negeri 12 Yogyakarta and measure their impact on the quality of education. The research method involved in-depth interviews with the school principal, Mr. Abdurrahman, observations in the school environment, and analysis of documents related to school leadership policies. The collected data was analyzed qualitatively to identify the results-based leadership strategies implemented and their impact on learning. This case study reflects successful leadership practices in increasing student achievement, developing a dynamic learning culture, and motivating school staff. The results of this research show that the application of results-based leadership techniques has succeeded in improving the quality of education at SMP Negeri 12 Yogyakarta. Principals who implement results-based leadership have created a school environment that focuses on achieving better results, student motivation, and innovation in learning. The conclusion of this research is that results-based leadership can be an effective model in managing schools and improving the quality of education. The practical guide prepared based on the findings of this research can be a reference for educational leaders to strengthen results-based leadership practices in the continuously developing Indonesian educational context.